2016
DOI: 10.1016/j.heares.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Hearing sensitivity differs between zebrafish lines used in auditory research

Abstract: Zebrafish are increasingly used in auditory studies, in part due to the development of several transgenic lines that express hair cell-specific fluorescent proteins. However, it is largely unknown how transgene expression influences auditory phenotype. We previously observed reduced auditory sensitivity in adult Brn3c:mGFP transgenic zebrafish, which express membrane-bound green fluorescent protein (GFP) in sensory hair cells. Here, we examine the auditory sensitivity of zebrafish from multiple transgenic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 90 publications
1
24
1
Order By: Relevance
“…1 μPa). These thresholds were about 20-30 dB lower than previously reported audiograms for other AB lines (Monroe et al, 2016;Wang et al, 2015). Such differences might be related to the acoustic isolation period adopted in this study before audiometry, different setup configurations (i.e.…”
Section: Noise-induced Hearing Loss In Zebrafishcontrasting
confidence: 66%
See 2 more Smart Citations
“…1 μPa). These thresholds were about 20-30 dB lower than previously reported audiograms for other AB lines (Monroe et al, 2016;Wang et al, 2015). Such differences might be related to the acoustic isolation period adopted in this study before audiometry, different setup configurations (i.e.…”
Section: Noise-induced Hearing Loss In Zebrafishcontrasting
confidence: 66%
“…shorter distance between subject and underwater speaker in our system that may result in higher particle motion component), distinct setup calibration procedures and SPL determination, and probably sensitivity differences between AB lines. Nevertheless, the overall shape of our baseline audiogram and best response frequencies were similar to prior studies using similar AEP recording procedures (Monroe et al, 2016;Wang et al, 2015). We have also adopted a criterion for threshold determination based on the visual inspection of the AEP responses, which may be more subjective than alternative methods including comparison between AEP amplitude and controlled residual noise to set specific threshold criteria (Xiao & Braun, 2008).…”
Section: Noise-induced Hearing Loss In Zebrafishmentioning
confidence: 65%
See 1 more Smart Citation
“…To our knowledge, this is the first report of a strain difference in aminoglycoside susceptibility in zebrafish. Monroe et al (2016) demonstrated that different strains of adult zebrafish differ in hearing sensitivity, with TL fish having greater sensitivity than age-matched ∗ ABs. However, the cause of these differences is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear to what extent observed differences in zebrafish characteristics and behavior are due to genetics, as opposed to individual laboratory and husbandry practices (Ball et al, 2014). Strain-specific behavioral responses to various stimuli have been documented (Vignet et al, 2013;Gao et al, 2016;Quadros et al, 2016;Seguret et al, 2016;van den Bos et al, 2017), including differences in hearing sensitivity (Monroe et al, 2016), visual social preference (Barba-Escobedo and Gould, 2012), and growth performance in response to fasting (Meyer et al, 2013). To date, there is little evidence to indicate the existence of strain differences in sensitivity to toxicants (Chatla et al, 2016), or how genetic differences affect responses to toxicants (Coe et al, 2009).…”
Section: Source and Strain Of Fish Usedmentioning
confidence: 99%